Выражение: ( x + 2) (x^2 - 2x + 4) - x(x + 2) (x - 2) покажите, что значение выражения ( x + 2) (x^2 - 2x + 4) - x(x + 2) (x - 2) при x = 1 равно 12.

aksenovazlata aksenovazlata    2   12.03.2019 19:37    2

Ответы
alena7571 alena7571  25.05.2020 02:42

Упростим выражение:

(x + 2) (x² - 2x + 4) - x(x + 2) (x - 2) =

= (x + 2) (x² - 2x + 4 - x(x - 2)) =

= (x + 2) (x² - 2x + 4 - x² + 2x) =

= 4(x + 2)

Подставим значение х=1 :

4(1+2)=12, что и требовалось доказать.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра